Celecoxib for the prevention of nonmuscle invasive bladder cancer: results from a matched control study. (December 2015) - Pagliarulo, Vincenzo; Ancona, Patrizia; Martines, Ivan; Spadavecchia, Rossana; Di Stasi, Savino; Alba, Stefano; Cormio, Luigi; Fanizza, Caterina; Salerno, Annamaria; Carrieri, Giuseppe; Pagliarulo, Arcangelo
Objectives: New targets and approaches are under investigation for the treatment of nonmuscle invasive bladder cancer (NMIBC). Preclinical data suggest cyclooxygenase-2 (COX-2) as a promising target. Celecoxib, a COX-2 selective inhibitor, inhibits tumor development and enhances survival, both in vitro and in vivo models of bladder cancer. Therefore, we conducted a pilot study of celecoxib to prevent recurrence in patients with intermediate risk NMIBC. Methods: Treatment with celecoxib was administered orally for 12 months and compared with a contemporary series of patients treated with intravesical mitomycin C (MMC), given weekly for 4 weeks and then monthly for 11 months. Primary endpoints were time to first recurrence and adverse events. Results: From 2003 through 2006, 58 patients were treated with celecoxib and compared with 66 patients receiving MMC. After a median follow up of 75 months, 49 patients were disease free, including 23 (34.85%) in the MMC group and 26 (44.8%) in the celecoxib group. Median disease-free interval was 67 months [95% confidence interval (CI) 35.8 to NA] versus 41 months (95% CI 27.1–67.1; log-rank p = 0.25) for patients treated with MMC and celecoxib, respectively. In the multivariate analysis, treatment was not found to be an independent predictor for recurrence [hazard ratio (HR) 0.76, 95% CI 0.47–1.22, p = 0.25). Overall, 45 AEs were recorded in 35/124 patients. There were no differences between the two groups. Conclusions: Our data support a clinical benefit of celecoxib and encourage future trials in which COX-2 inhibitors may be tested in selected patients with NMIBC.